2018
DOI: 10.3390/cells7090134
|View full text |Cite
|
Sign up to set email alerts
|

Integration of miRNA and mRNA Co-Expression Reveals Potential Regulatory Roles of miRNAs in Developmental and Immunological Processes in Calf Ileum during Early Growth

Abstract: This study aimed to investigate the potential regulatory roles of miRNAs in calf ileum developmental transition from the pre- to the post-weaning period. For this purpose, ileum tissues were collected from eight calves at the pre-weaning period and another eight calves at the post-weaning period and miRNA expression characterized by miRNA sequencing, followed by functional analyses. A total of 388 miRNAs, including 81 novel miRNAs, were identified. A total of 220 miRNAs were differentially expressed (DE) betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…MicroRNAs have been shown to play a role in early calf development [46,47]. In the current study, differentially expressed miRNAs were found to be dysregulated in calves born to BLV-infected dams.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…MicroRNAs have been shown to play a role in early calf development [46,47]. In the current study, differentially expressed miRNAs were found to be dysregulated in calves born to BLV-infected dams.…”
Section: Discussionmentioning
confidence: 53%
“…Human and mouse orthologs of the four downregulated miRNAs (miR-1, miR-133a, miR-133b, and miR-206) have been shown to play roles in cardiac and skeletal muscle growth and differentiation [45][46][47]. Specifically, miR-1 targets the Hand2 transcription factor as well as HDAC4, which are necessary for cardiac development and muscle growth repression, respectively [48,49].…”
Section: Resultsmentioning
confidence: 99%
“…Further functional analysis revealed that these miRNA were involved in rumen development, immune regulation, and digestion processes, which were significantly regulated by bta-miR-145 and bta-miR-199a-3p. The authors also compared the miRNA expression profiles in the calf ileum between the two periods, and identified several miRNA-mRNA pairs such as bta-miR-374a-FBXO18, bta-miR-374a-GTPBP3, and bta-miR-374a-GNB2, which played crucial roles in ileum development, and bta-miR-15b-IKBKB, which was involved in immune functions [15]. These studies provided important information suggesting that the altered miRNAs caused by weaning stress were associated with tissue development and the development of the immune system.…”
Section: Introductionmentioning
confidence: 99%